Occupational therapy for children with severe cerebral palsy in government healthcare facilities in the Western Cape: an overview of current services - Fuller, Lauren (Division of Occupational Therapy, 2021)
Background: There is a high worldwide prevalence of cerebral palsy, a neurological condition which impacts most areas of life of children and their families. Evidence shows that occupational therapy is effective in enhancing the child's function, participation and quality of life, especially when provided at a young age and with high intensity. Literature provides additional recommendations for occupational therapy to follow a holistic and family-centred approach, considering participation in context, rather than an individual medical focus. These notions place pressure on the strained South African healthcare system, where human and physical resources, as well as contextually-relevant evidence for practice, are limited. The aim of this research was, therefore, to obtain a baseline description of the occupational therapy services being provided to children with severe cerebral palsy, across all government healthcare facilities of the Western Cape province. Methods: A quantitative, cross-sectional descriptive study was conducted, using a selfdesigned questionnaire. The questionnaire was developed using recognised survey principles in order to maintain research rigour, reliability and validity of results, and guidelines from previousstudies of a similar nature. The questionnaire was available to participants in duplicate online and hard copy formats. The anonymous, self-report questionnaire obtained profiles of the participating occupational therapists and their departments, descriptions of current service provision (assessments, goal-setting and interventions), perceived factors influencing service selection, and an understanding of services therapists felt they should be providing more of. No sampling took place and responses were invited from all occupational therapists employed by the provincial health department. All recruitment and correspondence took place via email or telephone. Recruitment and data collection took place over a period of 16 weeks, with each participant having a maximum of two weeks to submit their responses, after which a maximum of three reminders were sent. Numerical data were analysed using non-parametric descriptive statistics and categorical data were presented in terms of frequencies and percentages. Ethical principles adhered to included respect, confidentiality, anonymity, beneficence, non-maleficence and justice. Results: There was a response rate of 53%, with all provincial health districts and levels of care represented amongst participants. Assessments frequently involved observations of the child in activities(85%) and interviews with their caregiver (98%). Goals formulated, with some input of caregivers, related to occupational performance components (91%) more often than occupational performance (77%), and largely aimed to maintain the child's condition (68%), rather than improve development or functional participation (47%). A range of interventions were provided, but appointments were infrequent (median: 1 per month), mainly took place in clinical environments (100%), and waiting periods for assistive devices and orthotics were common. Opportunities for direct therapy and interventions in the child's daily context were limited, and home programmes and caregiver education were heavily relied upon indirect intervention methods, frequently implemented by 100% and 91% of participants respectively. Key factors influencing the selection of services included resource availability (62%), therapists' training (62%) and the level of care at which they worked (59%). Therapists felt they were meeting some of the children's needs, and required the support of the multidisciplinary team to meet more of their needs effectively. Conclusion: This study provides insight into occupational therapists' roles in the government healthcare sector in the Western Cape province, and highlights the degree of alignment of services with policy and elements of best practice. Some merits are clear, in terms of the combination of direct and indirect services provided and the involvement of families in therapy processes. However, there remains a shortfall in terms of effective holistic, evidence-based, family-centred, and early and intensive approaches. This study, therefore prompts revision of strategies to implement existing policies promoting quality services for people with disabilities and align occupational therapists' training with evidence-based practice and holistic frameworks and approaches. Further research is recommended, particularly a qualitative consideration of the contextual factors influencing service provision, in order to better understand and address the barriers to meaningful and effective services for this population within the context of Primary Healthcare. With these recommendations, quality service provision, leading to participation and quality of life outcomes for children with severe cerebral palsy and their families, may be enhanced.